1995
DOI: 10.1021/ma00123a001
|View full text |Cite
|
Sign up to set email alerts
|

A Real-Time Simultaneous Small- and Wide-Angle X-ray Scattering Study of In-Situ Deformation of Isotropic Polyethylene

Abstract: Smalland wide-angle X-ray scattering patterns were measured in real time during insitu deformation of isotropic polyethylene at room temperature. A linear low-density polyethylene (LLDPE) was compared with a high-density polyethylene (HDPE) of approximately the same molecular weight. SAXS showed that the start of cavitation in the HDPE coincided with the onset of a stress-induced martensitic transformation detected by WAXS at a low macroscopic strain (~0.06). It is proposed that the transformation mechanism wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
194
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(213 citation statements)
references
References 13 publications
18
194
1
Order By: Relevance
“…This is because the steric hindrance of the stacked crystalline blocks is enhanced by the increase of the rigid crystal structure within the blocks. No appreciable molecular-weight dependence is observed in the present study for the HDPE with relatively low molecular weights, which is consistent with IR and X-ray diffraction studies [37,46,47].…”
Section: Resultssupporting
confidence: 92%
“…This is because the steric hindrance of the stacked crystalline blocks is enhanced by the increase of the rigid crystal structure within the blocks. No appreciable molecular-weight dependence is observed in the present study for the HDPE with relatively low molecular weights, which is consistent with IR and X-ray diffraction studies [37,46,47].…”
Section: Resultssupporting
confidence: 92%
“…The amorphous halo for nanocomposites obtained by melt intercalation present smaller regions than for those obtained by solution intercalation. The lower viscosity of the medium in the solution intercalation method very probably allowed nanoparticles to get diffused more rapidly than in melt intercalation, in this way a more homogeneous dispersion of nanoparticles can be obtained and more CNTs or clays can act as sites for crystallization as already very well pointed out in the literature [22][23][24][25][26] . In addition, it can be observed a diffraction peak locates at 2Ξ=20° for the nanocomposites with CNT prepared by solution (PENCs).…”
Section: Influence Of Intercalation Methods In Properties Of Clay Andmentioning
confidence: 84%
“…This peak can be indexed as the plane (010) plane of the monoclinic form of PE 22 . In general, the monoclinic form of PE is metastable in pure polymers and is only obtained under either high pressure 23 or large deformations, for example, during mechanical stretching 24 , some authors also observed the formation of monoclinic PE crystals in nanocomposites with carbon nanotubes 25,26 . Zhang et al 26 affirmed that the formation of monoclinic PE crystals in nanocomposites with carbon nanotube demonstrates that the CNTs act as a nucleating agent for the monoclinic PE crystallization.…”
Section: Influence Of Intercalation Methods In Properties Of Clay Andmentioning
confidence: 99%
“…3,[15][16][17][18] Being composed of the interpenetrating networks built up by both crystalline lamellae and the entangled amorphous polymeric chains in between, semicrystalline polymers always exhibit a complex deformation behavior under tensile deformation. 1,[19][20][21][22][23] The behavior of the polymers during stretching is generally influenced by both the crystalline and the amorphous phases. 12,[24][25][26][27][28] The small-deformation properties are found to depend only on the nature of crystalline lamellae; whereas the ultimate properties are dominated by the entangled amorphous network.…”
Section: Introductionmentioning
confidence: 99%